Fractal and chaotic map-enhanced grey wolf optimization for robust fire detection in deep convolutional neural networks - Yassine Bouteraa; Mohammad Khishe (Scientific Reports)
Abstract This paper introduces a novel approach to enhancing the architecture of deep convolutional neural networks, addressing issues of self-design. The proposed strategy leverages the grey wolf optimizer and the multi-scale fractal chaotic map search scheme as fundamental components to enhance exploration and exploitation, thereby improving the classification task. Several experiments validate the method, demonstrating an impressive 87.37% accuracy across 95 random trials, outperforming 23 state-of-the-art classifiers in the study’s nine datasets. This work underscores the potential of chaotic/fractal and bio-inspired paradigms in advancing neural architecture.